Kepemimpinan Dan Pengawasan Di Program Studi Magister Manajemen Pendidikan Universitas Ahmad Dahlan Yogyakarta - Hasra; Subari; Nurhasanah; Eni Susilowati; Arif Rahman Hakim; Agustina Pitriyani; Akhmad (CV. Multi Kreasi Media, 2022)
In the context of higher education, leadership and supervision play a crucial role in ensuring the operational and academic success of a study program. Universitas Ahmad Dahlan, as one of Indonesia’s leading educational institutions, is strongly committed to continuously improving educational quality through effective and efficient management. The PPL Internship Activity Report provides an overview of leadership and supervision within the Master of Educational Management Program at Universitas Ahmad Dahlan, Yogyakarta. The PPL activities are designed to include preparation, implementation, evaluation, and reporting stages. Data collection methods include interviews, observation, and documentation. Collected data is analyzed interactively through data reduction, data presentation, and conclusion drawing.From the PPL activities conducted, it is evident that leadership and supervision in the Master of Educational Management Program at Universitas Ahmad Dahlan, Yogyakarta, are being implemented very well. Leadership in the program reflects a highly effective transformational leadership style through an inclusive and participatory approach, encouraging active involvement of lecturers and staff in the evaluation and decision-making processes, while also providing personal and empathetic attention to each team member to maximize their potential. Dr. Enung Hasanah, M.Pd’s leadership in PSMMP at Universitas Ahmad Dahlan, Yogyakarta, demonstrates high effectiveness in supervision, which aligns with the latest research findings.